Escaping the LRA: Examining the Decision to Disengage from Militarized Dissident Groups. Issue 2 (3rd April 2017) - Riley, John; Pearson, Kristin; Schneider, Mary Kate; Stimeling, Lindsey
ABSTRACT: This study seeks to understand the conditions that led individuals to accept the risks associated with leaving the Lord's Resistance Army. To this end, a large participant survey of former rebels was conducted. Results from the survey suggest that the investment model offers a useful tool for capturing the factors that weigh into an individual's decision-making process as he or she considers disengaging from a group. However, the data also suggest that lack of investment does not equate to disengagement. The perceived opportunity for escape and the costs associated with the risk of escape play critical roles. Consequently, counterinsurgency campaigns and postconflict reconciliation efforts in Africa ought to be jointly calibrated to maximize the likelihood of disengagement.